Effect of single-factor by ultrasound-assisted extraction on antioxidant properties of extract from jiaogulan (Gynostemma pentaphyllum) leaves - Kamkayan, Pichanan; Assatarakul, Kitipong (Journal of Food Technology, Siam University, 2021)
This study aimed to investigate the effect of single-factor by ultrasound-assisted extraction on the antioxidant properties of the extract from jiaogulan leaves. Four single-factors namely ethanol concentration (50-90% v/v), liquid to solid ratio (1:20-1:60 g/mL), extraction time (10-50 min) and amplitude (30-70%) were varied. It was found that all single-factors significantly affected antioxidant properties of the extract (p≤0.05). An increasing in antioxidant properties resulted from an increase in ethanol concentration, solid to liquid ratio, extraction time and amplitude. In addition, the best condition for jiaogulan leaves extraction were ethanol concentration of 70% v/v, solid to liquid ratio of 1:50 g/mL, extraction time of 20 min and amplitude of 40%. The extract obtained from such condition had total phenolic content, total flavonoid content and antioxidant activity with 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric ion reducing antioxidant power (FRAP) methods of 405.17 mg GAE/100 g dry wt., 2.59 mg QCE/100 g dry wt., 1881.07 mM trolox/100 g dry wt., and 2838.15 mM trolox/100 g dry wt., respectively.